2013
DOI: 10.1097/phm.0b013e31829b4d72
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided vs. Blind Steroid Injections in Carpal Tunnel Syndrome

Abstract: Although both US-guided and blind steroid injections were effective in reducing the symptoms of CTS and improving the function, an earlier onset/better improvement of symptom relief suggests that US-guided steroid injection may be more effective than are blind injections in CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 15 publications
6
87
2
4
Order By: Relevance
“…Üstün et al compared the efficacy and safety of US-guided versus blind steroid injections in 46 CTS patients (11). The authors concluded that although both US-guided and blind steroid injections were effective in reducing the symptoms of CTS and improving the function, an earlier Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Üstün et al compared the efficacy and safety of US-guided versus blind steroid injections in 46 CTS patients (11). The authors concluded that although both US-guided and blind steroid injections were effective in reducing the symptoms of CTS and improving the function, an earlier Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, injection under ultrasound (US) guidance may increase precision and therapeutic outcomes and decrease complication rates. There are only a few studies that have investigated US guidance for injections in CTS, and they generally determined that US-guided injections result in better symptom relief and increased and long-lasting therapeutic effects compared to blind injections (11)(12)(13). Since the studies in this area are limited in number, this study was conducted to compare the effectiveness of USguided injection versus blind injection of corticosteroids in the treatment of severe CTS according to symptom severity, hand function, and electrophysiological parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides a real-time anatomic, high-resolution image of the median nerve, the carpal tunnel, and the neighboring structures, and helps physicians to place the needle tip and inject closer to the median nerve accurately. Several previous studies have demonstrated higher effectiveness of ultrasound-guided injections in CTS when compared to blind injections [1,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is the most common compressive neuropathy of the upper extremity [1]. It has been estimated to occur in 3-4% of the general population with a predominance among the female gender [2].…”
Section: Introductionmentioning
confidence: 99%